Medical cleaning endoscope cap and preparation method thereof

By spraying modified nanopaint on the endoscope cap, the existing endoscope caps are solved, and other problems such as fogging and hanging during use are achieved, which achieves better field of vision clarity and antibacteriality, and improves surgical safety and efficiency.

CN119564945APending Publication Date: 2025-03-07HUAINAN UNITED UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411792594.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-07
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing endoscopic caps have problems such as fogging and hanging during use, and are not hydrophilic, anti-fog, anti-swelling and antibacterial properties, which affect the surgical field and safety.

Method used

Using nanocoating, C/P doped-porous NH2-TiO2/SiO2 nanomicrospheres are modified by surfactant and silane coupling agent, and sprayed on the surface of the endoscope cap to form a self-cleaning coating to improve anti-reflection and impermeability.

Benefits of technology

It effectively prevents fogging and hanging, improves the field of view of the endoscope, has good antibacterial properties, reduces the risk of infection, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175714320000131
    Figure BDA0005175714320000131
  • Figure BDA0005175714320000141
    Figure BDA0005175714320000141
  • Figure BDA0005175714320000142
    Figure BDA0005175714320000142
Patent Text Reader

Abstract

The invention provides a medical cleaning endoscope cap and a preparation method thereof, and belongs to the technical field of medical instruments. A nano coating is uniformly sprayed on the surface of the cleaning endoscope cap, the cleaning endoscope cap is dried and cured to form a coating, the medical cleaning endoscope cap is prepared, and the nano coating is a coating containing C / P doped porous NH2-TiO2 / SiO2 nano microspheres modified by a surfactant and a silane coupling agent and a dispersing agent. The medical cleaning endoscope cap prepared by the invention has a self-cleaning effect, effectively prevents the problems of fogging, hanging and the like, has the characteristics of better anti-reflection performance and refraction changing performance, has a better anti-reflection effect, improves the visual field of an endoscope, also has better antibacterial property, reduces the infection risk, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical instruments, and in particular to a medical clean endoscope cap and a preparation method thereof. Background Art

[0002] Medical clean endoscope cap, also known as endoscope tip cap, is a medical device used to protect the tip of the endoscope and maintain an appropriate endoscopic field of view. It is commonly used in digestive endoscopy and EMR (endoscopic mucosal resection), ESD (endoscopic mucosal dissection), POEM (peroral endoscopic myotomy) and other surgeries. It is usually made of polymer materials such as thermoplastic polyurethane (TPU), sterilized with ethylene oxide, and disposable. The principle of the product is to avoid the influence of blood, mist, and mucus on doctors during endoscopic (arthroscopy, laparoscopy, etc.) surgery through a special medical coating, thereby improving the quality of surgery.

[0003] This product has the following advantages: providing more working space to assist in lifting or attracting tissue during resection; avoiding scratches on tissue by the hard front end of the endoscope; smooth surface and moderate elasticity; compatible with a variety of endoscopes; providing a clear field of view, made of medical-quality transparent materials to improve imaging quality; reducing the risk of cross-infection and preventing the endoscope from coming into contact with patient body fluids or other contaminants; easy to clean and disinfect, usually with a detachable design; ensuring an unobstructed field of view during surgery, improving surgical efficiency, shortening surgical time by about 20%, and ensuring that the endoscope lens is not infected; easy to disassemble and install; and completely solving the previous steps of cleaning the field of view such as wiping the lens with iodine during surgery.

[0004] Currently, the endoscope cap products on the market are not coated, and their hydrophilicity, anti-fog, anti-dripping and antibacterial properties are poor. Summary of the invention

[0005] The purpose of the present invention is to propose a medical clean endoscope cap and a preparation method thereof, which has a self-cleaning effect, effectively prevents problems such as fogging and hanging, has good anti-reflection and refractive performance change characteristics, and thus has a good anti-transmission effect, thereby improving the field of view of the endoscope, and also has good antibacterial properties, reduces the risk of infection, and has broad application prospects.

[0006] The technical solution of the present invention is achieved in this way:

[0007] The invention provides a method for preparing a medical clean endoscope cap. Nano coating is uniformly sprayed on the surface of the clean endoscope cap, and dried and solidified to form a coating to prepare the medical clean endoscope cap. The nano coating is a coating containing C / P doped-porous NH2-TiO2 / SiO2 nano-microspheres modified by a surfactant and a silane coupling agent and a dispersant.

[0008] As a further improvement of the present invention, the preparation method of the nano coating is as follows:

[0009] S1. dissolving aminosilane, tetrabutyl titanate and a lipophilic emulsifier in an organic solvent to obtain an oil phase; dissolving a porogen and a hydrophilic surfactant in water to obtain an aqueous phase; dropping the aqueous phase into the oil phase, emulsifying, centrifuging, washing, drying and calcining to obtain porous NH2-TiO2 / SiO2 nanospheres;

[0010] S2. The porous NH2-TiO2 / SiO2 nanospheres were added to water, phytic acid was added, impregnated, centrifuged, washed, dried, and calcined to obtain C / P doped - porous NH2-TiO2 / SiO2 nanospheres;

[0011] S3. Add C / P doped-porous NH2-TiO2 / SiO2 nanospheres to acetonitrile, add N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride, stir to react, centrifuge, wash, and dry to obtain surfactant-modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0012] S4. The surfactant-modified C / P-doped - porous NH2-TiO2 / SiO2 nanospheres were added to ethanol, a silane coupling agent was added, the reaction was heated and stirred, centrifuged, washed, and dried to obtain modified C / P-doped - porous NH2-TiO2 / SiO2 nanospheres;

[0013] S5. Add the modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres and dispersant into water, disperse them evenly by ultrasonication, and prepare nano coating.

[0014] As a further improvement of the present invention, the mass ratio of the aminosilane, tetrabutyl titanate, lipophilic emulsifier, porogen and hydrophilic surfactant in step S1 is 7-10:4-6:0.5-1:1-2:0.5-1, the lipophilic emulsifier is selected from at least one of Span-20, Span-40, Span-60, Span-80 and Span-85, the hydrophilic emulsifier is selected from at least one of Tween-20, Tween-40, Tween-60, Tween-80 and Tween-85, the aminosilane is selected from γ-aminopropyl At least one of trimethoxysilane, γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane, and diethylenetriaminopropyltrimethoxysilane, the porogen is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide, the calcination temperature is 400-600° C., and the time is 2-4.

[0015] As a further improvement of the present invention, in step S2, the mass ratio of the porous NH2-TiO2 / SiO2 nanospheres and phytic acid is 10:1-2, the impregnation time is 30-50 minutes, the calcination temperature is 800-900°C, and the time is 1-3 hours.

[0016] As a further improvement of the present invention, in step S3, the mass ratio of the C / P doped-porous NH2-TiO2 / SiO2 nanospheres and N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride is 10:3-4, and the stirring reaction time is 7-10 hours.

[0017] As a further improvement of the present invention, in step S4, the mass ratio of the surfactant-modified C / P-doped-porous NH2-TiO2 / SiO2 nanospheres and the silane coupling agent with an epoxy group is 10:2-3, the temperature of the heating and stirring reaction is 45-55°C, the time is 2-4h, and the silane coupling agent is selected from at least one of KH560, KH550, KH602, and KH792.

[0018] As a further improvement of the present invention, the silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10:3-5.

[0019] As a further improvement of the present invention, the mass ratio of the modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres and the dispersant in step S5 is 10:1-2, the dispersant is selected from at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and sodium citrate, the power of the ultrasonic dispersion is 1000-2000W, and the time is 20-30min.

[0020] As a further improvement of the present invention, the spraying amount of the nano coating is 0.5-1g / cm 2 .

[0021] The present invention further protects a medical clean endoscope cap prepared by the above preparation method.

[0022] The present invention has the following beneficial effects:

[0023] The present invention adopts sol-gel reaction to prepare a porous TiO2 / SiO2 nano-microsphere with amino group, which has a rough hydrophilic surface. The hydrophilic surface becomes more hydrophilic as the roughness increases, thereby greatly improving the hydrophilicity of the coating surface. At the same time, it has the dual functions of self-cleaning and anti-reflection, avoiding the influence of refraction and reflection of light on the field of view of the endoscope, greatly improving the clarity of the endoscope, and having good durability.

[0024] Titanium dioxide has good photocatalytic antibacterial properties, but its ability to utilize visible light is relatively poor, which greatly limits its application. The present invention impregnates phytic acid, calcines at high temperatures and then carbonizes the obtained C / P-doped titanium dioxide lattice, which, on the one hand, greatly improves its light stability, and on the other hand, improves its utilization efficiency of sunlight and visible light, thereby greatly improving the antibacterial effect of the coating.

[0025] The present invention further couples the surface of the prepared C / P doped-porous NH2-TiO2 / SiO2 nano-microspheres with the epoxy group of the surfactant N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl) ammonium chloride through a reaction of the amino group, so that the surface of the nano-microspheres has a surface active structure, which greatly reduces the surface energy of the coating, makes it difficult for water and pollutants to adhere to the surface, has a self-cleaning effect, and effectively prevents problems such as fogging and retention.

[0026] The surface of the surfactant-modified C / P-doped porous NH2-TiO2 / SiO2 nano-microspheres prepared in the present invention is modified by a silane coupling agent, and the nano-microspheres have epoxy groups and amino groups, and can be bonded to the surface of a clean endoscope cap made of polyurethane material through a ring-opening reaction and the formation of hydrogen bonds, thereby greatly improving the adhesion of the coating and the durability of the prepared medical clean endoscope cap. At the same time, the nano-coating has good anti-reflection and refractive performance change characteristics, thereby having a good anti-reflection effect.

[0027] The medical clean endoscope cap prepared by the present invention has a self-cleaning effect, effectively prevents problems such as fogging and hanging, has good anti-reflection and refractive performance change characteristics, and thus has a good anti-transmission effect, thereby improving the field of view of the endoscope, and also has good antibacterial properties, reduces the risk of infection, and has broad application prospects. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Preparation Example 1

[0030] This preparation example provides a medical clean endoscope cap, comprising the following steps:

[0031] S1. Dissolve 7g of γ-aminopropyltrimethoxysilane, 4g of tetrabutyl titanate, and 0.5g of Span-40 in 200mL of dichloromethane to obtain an oil phase; dissolve 1g of hexadecyltrimethylammonium bromide and 0.5g of Tween-40 in 100mL of water to obtain an aqueous phase; dropwise add the aqueous phase to the oil phase, emulsify at 8000r / min for 15min, stir and react for 7h, centrifuge, wash, dry, and calcine at 400°C for 2h to obtain porous NH2-TiO2 / SiO2 nanospheres;

[0032] S2. 10 g of porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of water, 1 g of phytic acid was added, immersed for 30 min, centrifuged, washed, dried, and calcined at 800 ° C for 1 h to obtain C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0033] S3. 10 g of C / P doped-porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of acetonitrile, 3 g of N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride was added, the reaction was stirred for 7-10 h, centrifuged, washed, and dried to obtain surfactant-modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0034] S4. 10 g of surfactant-modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of ethanol, 2 g of silane coupling agent was added, heated to 45 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres;

[0035] The silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10:3;

[0036] S5. Add 10 g of modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres and 1 g of hexadecyltrimethylammonium bromide to 100 mL of water, and disperse them ultrasonically at 1000 W for 20 min to obtain a nanocoating.

[0037] Preparation Example 2

[0038] This preparation example provides a medical clean endoscope cap, comprising the following steps:

[0039] S1. Dissolve 10g N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, 6g tetrabutyl titanate, and 1g Span-60 in 200mL dichloromethane to obtain an oil phase; dissolve 2g hexadecyltrimethylammonium chloride and 1g Tween-60 in 100mL water to obtain an aqueous phase; dropwise add the aqueous phase to the oil phase, emulsify at 8000r / min for 15min, stir and react for 7h, centrifuge, wash, dry, and calcine at 600℃ for 4h to obtain porous NH2-TiO2 / SiO2 nanospheres;

[0040] S2. 10 g of porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of water, 2 g of phytic acid was added, immersed for 50 min, centrifuged, washed, dried, and calcined at 900 ° C for 3 h to obtain C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0041] S3. 10 g of C / P doped-porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of acetonitrile, 4 g of N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride was added, the reaction was stirred for 10 h, centrifuged, washed, and dried to obtain surfactant-modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0042] S4. 10 g of surfactant-modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of ethanol, 3 g of silane coupling agent was added, heated to 55 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres;

[0043] The silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10:5;

[0044] S5. Add 10 g of modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres and 2 g of sodium dodecyl sulfate to 100 mL of water, and disperse them ultrasonically at 2000 W for 30 min to obtain a nanocoating.

[0045] Preparation Example 3

[0046] This preparation example provides a medical clean endoscope cap, comprising the following steps:

[0047] S1. 8 g of N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, 5 g of tetrabutyl titanate, and 0.7 g of Span-85 were dissolved in 200 mL of dichloromethane to obtain an oil phase; 1.5 g of hexadecyltrimethylammonium bromide and 0.7 g of Tween-85 were dissolved in 100 mL of water to obtain an aqueous phase; the aqueous phase was added dropwise to the oil phase, emulsified at 8000 r / min for 15 min, stirred for reaction for 7 h, centrifuged, washed, dried, and calcined at 500 ° C for 3 h to obtain porous NH2-TiO2 / SiO2 nanospheres;

[0048] S2. 10 g of porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of water, 1.5 g of phytic acid was added, immersed for 40 min, centrifuged, washed, dried, and calcined at 850 ° C for 2 h to obtain C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0049] S3. 10 g of C / P doped-porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of acetonitrile, 3.5 g of N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride was added, the reaction was stirred for 8 h, centrifuged, washed, and dried to obtain surfactant-modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0050] S4. 10 g of surfactant-modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of ethanol, 2.5 g of a silane coupling agent was added, the mixture was heated to 50 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres;

[0051] The silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10:4;

[0052] S5. Add 10 g of modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres and 1.5 g of polyvinyl pyrrolidone into 100 mL of water, and disperse them ultrasonically at 1500 W for 25 min to obtain a nanocoating.

[0053] Preparation Example 4

[0054] Compared with Preparation Example 3, the difference is that the silane coupling agent is a single KH560.

[0055] Preparation Example 5

[0056] Compared with Preparation Example 3, the difference is that the silane coupling agent is a single KH550.

[0057] Comparative Preparation Example 1

[0058] Compared with Preparation Example 3, the difference is that cetyltrimethylammonium bromide is not added in step S1.

[0059] The details are as follows:

[0060] S1. Dissolve 8g N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane, 5g tetrabutyl titanate, and 0.7g Span-85 in 200mL dichloromethane to obtain an oil phase; dissolve 0.7g Tween-85 in 100mL water to obtain an aqueous phase; add the aqueous phase dropwise into the oil phase, emulsify at 8000r / min for 15min, stir to react for 7h, centrifuge, wash, dry, and calcine at 500℃ for 3h to obtain NH2-TiO2 / SiO2 nanospheres.

[0061] Comparative Preparation Example 2

[0062] Compared with Preparation Example 3, the difference is that N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane is not added in step S1.

[0063] The details are as follows:

[0064] S1. Dissolve 13g of tetrabutyl titanate and 0.7g of Span-85 in 200mL of dichloromethane to obtain an oil phase; dissolve 1.5g of hexadecyltrimethylammonium bromide and 0.7g of Tween-85 in 100mL of water to obtain an aqueous phase; add the aqueous phase dropwise into the oil phase, emulsify at 8000r / min for 15min, stir and react for 7h, centrifuge, wash, dry, and calcine at 500℃ for 3h to obtain porous TiO2 nanospheres.

[0065] Comparative Preparation Example 3

[0066] Compared with Preparation Example 3, the difference is that tetrabutyl titanate is not added in step S1.

[0067] The details are as follows:

[0068] S1. Dissolve 13g N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane and 0.7g Span-85 in 200mL dichloromethane to obtain an oil phase; dissolve 1.5g hexadecyltrimethylammonium bromide and 0.7g Tween-85 in 100mL water to obtain an aqueous phase; add the aqueous phase dropwise into the oil phase, emulsify at 8000r / min for 15min, stir and react for 7h, centrifuge, wash, dry, and calcine at 500℃ for 3h to obtain porous NH2-SiO2 nanospheres.

[0069] Comparative Preparation Example 4

[0070] Compared with Preparation Example 3, the difference is that step S2 is not performed.

[0071] The details are as follows:

[0072] S1. 8 g of N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, 5 g of tetrabutyl titanate, and 0.7 g of Span-85 were dissolved in 200 mL of dichloromethane to obtain an oil phase; 1.5 g of hexadecyltrimethylammonium bromide and 0.7 g of Tween-85 were dissolved in 100 mL of water to obtain an aqueous phase; the aqueous phase was added dropwise to the oil phase, emulsified at 8000 r / min for 15 min, stirred for reaction for 7 h, centrifuged, washed, dried, and calcined at 500 ° C for 3 h to obtain porous NH2-TiO2 / SiO2 nanospheres;

[0073] S2. 10 g of porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of acetonitrile, and 3.5 g of N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride was added, and the mixture was stirred for 8 h, centrifuged, washed, and dried to obtain surfactant-modified porous NH2-TiO2 / SiO2 nanospheres;

[0074] S3. 10 g of surfactant-modified porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of ethanol, 2.5 g of a silane coupling agent was added, the mixture was heated to 50 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified porous NH2-TiO2 / SiO2 nanospheres;

[0075] The silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10:4;

[0076] S4. Add 10 g of modified porous NH2-TiO2 / SiO2 nanospheres and 1.5 g of polyvinyl pyrrolidone into 100 mL of water, and disperse them ultrasonically at 1500 W for 25 min to obtain a nanocoating.

[0077] Comparative Preparation Example 5

[0078] Compared with Preparation Example 3, the difference is that step S3 is not performed.

[0079] The details are as follows:

[0080] S1. 8 g of N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, 5 g of tetrabutyl titanate, and 0.7 g of Span-85 were dissolved in 200 mL of dichloromethane to obtain an oil phase; 1.5 g of hexadecyltrimethylammonium bromide and 0.7 g of Tween-85 were dissolved in 100 mL of water to obtain an aqueous phase; the aqueous phase was added dropwise to the oil phase, emulsified at 8000 r / min for 15 min, stirred for reaction for 7 h, centrifuged, washed, dried, and calcined at 500 ° C for 3 h to obtain porous NH2-TiO2 / SiO2 nanospheres;

[0081] S2. 10 g of porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of water, 1.5 g of phytic acid was added, immersed for 40 min, centrifuged, washed, dried, and calcined at 850 ° C for 2 h to obtain C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0082] S3. 10 g of C / P doped-porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of ethanol, 2.5 g of silane coupling agent was added, heated to 50 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0083] The silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10:4;

[0084] S4. Add 10 g of modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres and 1.5 g of polyvinyl pyrrolidone into 100 mL of water, and disperse them ultrasonically at 1500 W for 25 min to obtain a nanocoating.

[0085] Comparative Preparation Example 6

[0086] Compared with Preparation Example 3, the difference is that step S4 is not performed.

[0087] The details are as follows:

[0088] S1. 8 g of N-β (aminoethyl) -γ-aminopropylmethyldimethoxysilane, 5 g of tetrabutyl titanate, and 0.7 g of Span-85 were dissolved in 200 mL of dichloromethane to obtain an oil phase; 1.5 g of hexadecyltrimethylammonium bromide and 0.7 g of Tween-85 were dissolved in 100 mL of water to obtain an aqueous phase; the aqueous phase was added dropwise to the oil phase, emulsified at 8000 r / min for 15 min, stirred for reaction for 7 h, centrifuged, washed, dried, and calcined at 500 ° C for 3 h to obtain porous NH2-TiO2 / SiO2 nanospheres;

[0089] S2. 10 g of porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of water, 1.5 g of phytic acid was added, immersed for 40 min, centrifuged, washed, dried, and calcined at 850 ° C for 2 h to obtain C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0090] S3. 10 g of C / P doped-porous NH2-TiO2 / SiO2 nanospheres were added to 200 mL of acetonitrile, and 3.5 g of N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride was added, and the reaction was stirred for 8 h, centrifuged, washed, and dried to obtain surfactant-modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres;

[0091] S4. Add 10g of surfactant-modified C / P-doped-porous NH2-TiO2 / SiO2 nanospheres and 1.5g of polyvinyl pyrrolidone to 100mL of water, and ultrasonically disperse at 1500W for 25min to obtain a nanocoating.

[0092] Example 1

[0093] The nano coating prepared in Example 1 was uniformly sprayed on the surface of the clean endoscope cap, with a spraying amount of 0.7 g / cm 2 , dried at 60°C for 2h, and cured to form a coating to obtain a medical clean endoscope cap.

[0094] Example 2

[0095] The nano coating prepared in Example 2 was uniformly sprayed on the surface of the clean endoscope cap, with a spraying amount of 0.7 g / cm 2 , dried at 60°C for 2h, and cured to form a coating to obtain a medical clean endoscope cap.

[0096] Example 3

[0097] The nano coating prepared in Example 3 was uniformly sprayed on the surface of the clean endoscope cap, with a spraying amount of 0.7 g / cm 2 , dried at 60°C for 2h, and cured to form a coating to obtain a medical clean endoscope cap.

[0098] Example 4

[0099] Compared with Example 3, the difference is that the nano coating is prepared by Preparation Example 4.

[0100] Example 5

[0101] Compared with Example 3, the difference is that the nano coating is prepared by Preparation Example 5.

[0102] Comparative Example 1

[0103] Compared with Example 3, the difference is that the nano coating is prepared by Comparative Preparation Example 1.

[0104] Comparative Example 2

[0105] Compared with Example 3, the difference is that the nano coating is prepared by Comparative Preparation Example 2.

[0106] Comparative Example 3

[0107] Compared with Example 3, the difference is that the nano coating is prepared by Comparative Preparation Example 3.

[0108] Comparative Example 4

[0109] Compared with Example 3, the difference is that the nano coating is prepared by Comparative Preparation Example 4.

[0110] Comparative Example 5

[0111] Compared with Example 3, the difference is that the nano coating is prepared by Comparative Preparation Example 5.

[0112] Comparative Example 6

[0113] Compared with Example 3, the difference is that the nano coating is prepared by Comparative Preparation Example 6.

[0114] Test Example 1

[0115] The surface coatings of the medical clean endoscope caps prepared in Examples 1-3 of the present invention and Comparative Examples 1-6 were tested.

[0116] The results are shown in Table 1.

[0117] Table 1

[0118]

[0119]

[0120] It can be seen from the above table that the surface coating of the medical clean endoscope caps prepared in Examples 1-3 of the present invention has good adhesion, flexibility, stain resistance, self-cleaning and impact resistance.

[0121] Test Example 2

[0122] The surface coatings of the medical clean endoscope caps prepared in Examples 1-3 of the present invention and Comparative Examples 1-6 were tested for average light transmittance under the condition of visible light of 400-700 nm.

[0123] The results are shown in Table 2.

[0124] Table 2

[0125]

[0126]

[0127] It can be seen from the above table that the surface coating of the medical clean endoscope caps prepared in Examples 1-3 of the present invention has a good anti-reflection effect.

[0128] Test Example 3

[0129] According to the standard of GB / T21866-2008, take 0.5mL of the solution with a concentration of (5-10)×10 5cfu / mL of activated Escherichia coli (ATCC25922) bacterial suspension was dropped on the surface coating of the negative control clean endoscope cap and the medical clean endoscope caps prepared in Examples 1-3 of the present invention and Comparative Examples 1-6 to make the bacteria evenly contact the sample, and placed in a sterilized culture dish. After contacting for 24 hours in a constant temperature and humidity incubator at a temperature of 37°C and a relative humidity of >90%, the sample was rinsed with a washing solution, the bacteria obtained by rinsing were diluted and inoculated into a nutrient agar medium, and the live bacteria were counted after culturing in a constant temperature and humidity incubator for 24 hours.

[0130] The calculation formula of antibacterial rate is as follows:

[0131] Antibacterial rate (%) = (BC) / B × 100%

[0132] Among them, B is the colony count of the negative control group, and C is the colony count of the test coating.

[0133] The results are shown in Table 3.

[0134] Table 3

[0135]

[0136]

[0137] It can be seen from the above table that the surface coating of the medical clean endoscope caps prepared in Examples 1-3 of the present invention has good antibacterial properties.

[0138] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a medical clean endoscope cap, characterized in that: The nano coating is uniformly sprayed on the surface of a clean endoscope cap, dried and solidified to form a coating, and a medical clean endoscope cap is prepared. The nano coating is a coating containing C / P doped-porous NH2-TiO2 / SiO2 nano-microspheres modified by a surfactant and a silane coupling agent and a dispersant.

2. The preparation method according to claim 1, characterized in that: The preparation method of the nano coating is as follows: S1. dissolving aminosilane, tetrabutyl titanate and a lipophilic emulsifier in an organic solvent to obtain an oil phase; dissolving a porogen and a hydrophilic surfactant in water to obtain an aqueous phase; dropping the aqueous phase into the oil phase, emulsifying, centrifuging, washing, drying and calcining to obtain porous NH2-TiO2 / SiO2 nanospheres; S2. The porous NH2-TiO2 / SiO2 nanospheres were added to water, phytic acid was added, impregnated, centrifuged, washed, dried, and calcined to obtain C / P doped - porous NH2-TiO2 / SiO2 nanospheres; S3. Add C / P doped-porous NH2-TiO2 / SiO2 nanospheres to acetonitrile, add N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride, stir to react, centrifuge, wash, and dry to obtain surfactant-modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres; S4. The surfactant-modified C / P-doped - porous NH2-TiO2 / SiO2 nanospheres were added to ethanol, a silane coupling agent was added, the reaction was heated and stirred, centrifuged, washed, and dried to obtain modified C / P-doped - porous NH2-TiO2 / SiO2 nanospheres; S5. Add the modified C / P-doped porous NH2-TiO2 / SiO2 nanospheres and dispersant into water, disperse them evenly by ultrasonication, and prepare nano coating.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the aminosilane, tetrabutyl titanate, lipophilic emulsifier, porogen and hydrophilic surfactant in step S1 is 7-10:4-6:0.5-1:1-2:0.5-1, the lipophilic emulsifier is selected from at least one of Span-20, Span-40, Span-60, Span-80 and Span-85, the hydrophilic emulsifier is selected from at least one of Tween-20, Tween-40, Tween-60, Tween-80 and Tween-85, and the aminosilane is selected from γ-aminopropyltrimethoxysilane , at least one of γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane, and diethylenetriaminopropyltrimethoxysilane, the porogen is hexadecyltrimethylammonium chloride or hexadecyltrimethylammonium bromide, the calcination temperature is 400-600°C, and the time is 2-4h.

4. The preparation method according to claim 2, characterized in that: In step S2, the mass ratio of the porous NH2-TiO2 / SiO2 nanospheres to phytic acid is 10:1-2, the impregnation time is 30-50 minutes, the calcination temperature is 800-900°C, and the calcination time is 1-3 hours.

5. The preparation method according to claim 2, characterized in that: In step S3, the mass ratio of the C / P doped-porous NH2-TiO2 / SiO2 nanospheres and N-alkyl-N,N-dimethyl-N-(2,3-epoxypropyl)ammonium chloride is 10:3-4, and the stirring reaction time is 7-10 hours.

6. The preparation method according to claim 2, characterized in that: In step S4, the mass ratio of the surfactant-modified C / P-doped-porous NH2-TiO2 / SiO2 nanospheres and the silane coupling agent with an epoxy group is 10:2-3, the temperature of the heating and stirring reaction is 45-55°C, the time is 2-4h, and the silane coupling agent is selected from at least one of KH560, KH550, KH602, and KH792.

7. The preparation method according to claim 6, characterized in that: The silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10:3-5.

8. The preparation method according to claim 2, characterized in that: In step S5, the mass ratio of the modified C / P doped-porous NH2-TiO2 / SiO2 nanospheres and the dispersant is 10:1-2, the dispersant is selected from at least one of polyvinyl pyrrolidone, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and sodium citrate, the power of the ultrasonic dispersion is 1000-2000W, and the time is 20-30min.

9. The preparation method according to claim 1, characterized in that: The spraying amount of the nano coating is 0.5-1g / cm 2 .

10. A medical clean endoscope cap made by the preparation method according to any one of claims 1 to 9.